Studi Agenda Setting Film Silenced Terhadap Agenda Kebijakan Tentang Kejahatan Seksual Di Korea Selatan - Yunantari Dewi, Ni Made; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT Film as a mass media is a tool that is used to spread a message to the community. Can also be used to channel various ideas and it can also bring up a plurality of effects after it is aired. One of South Korean Film that brought up an effect after its screening is Silenced. Through qualitative research methods with literature study, researcher found an agenda setting process from Silenced towards the South Korean government policy’s agenda about sexual crime. Media’s agenda brought up a sexual abused issue that is interacting with public of South Korea’s agenda then interacts with the government policy’s agenda about sexual crime. This shows that Silenced Film’s agenda setting has a connection with South Korean government policy’s agenda about sexual crime. Keywords: South Korea, Film, Sexual Crime, Agenda Setting